Smoking under the tsars : a history of tobacco in imperial Russia - Starks, Tricia, 1969- (Ithaca ; London : Cornell University Press, 2018)
"Using unusual sources and approaching tobacco from the perspective of users, producers, and objectors, this monograph provides a view of the early transfer by the Russian market to smoking and presents the addictive, nicotine-soaked Russian cigarette - the papirosa - and the sensory, medical, social, cultural, and gendered consequences of this unique style of tobacco use"--
Introduction : papirosy and dependence -- Cultivated : exotic blends and imperial designs -- Produced : tobacco queens and working girls -- Tasted : distinctive smoking and social inclusion -- Condemned : social danger and neurasthenic decline -- Contested : health dispute and public disbelief -- Epilogue : revolution and cessation.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
JSTOR
Keywords: Smoking -- Russia -- History -- 19th century; Russians -- Tobacco use -- History; Tobacco -- Social aspects -- Russia -- History; Russia -- Social conditions -- 1801-1917.; Tabagisme -- Russie -- Histoire -- 19e siècle.; Russes -- Tabagisme -- Histoire; Tabac -- Aspect social -- Russie -- Histoire; Russie -- Conditions sociales -- 1801-1917.; SOCIAL SCIENCE -- Agriculture & Food; HISTORY -- Europe -- Russia & the Former Soviet Union; Smoking; Social conditions; Tobacco -- Social aspects; Russia; 1800-1917; History